Robula+: an algorithm for generating robust XPath locators for web testing. Issue 3 (9th March 2016) - Leotta, Maurizio; Stocco, Andrea; Ricca, Filippo; Tonella, Paolo
Abstract: Automated test scripts are used with success in many web development projects, so as to automatically verify key functionalities of the web application under test, reveal possible regressions and run a large number of tests in short time. However, the adoption of automated web testing brings advantages but also novel problems, among which the test code fragility problem. During the evolution of the web application, existing test code may easily break and testers have to correct it. In the context of automated DOM‐based web testing, one of the major costs for evolving the test code is the manual effort necessary to repair broken web page element locators – lines of source code identifying the web elements (e.g. form fields and buttons) to interact with. In this work, we presentRobula+, a novel algorithm able to generate robust XPath‐based locators – locators that are likely to work correctly on new releases of the web application. We comparedRobula+ with several state of the practice/art XPath locator generator tools/algorithms. Results show that XPath locators produced byRobula+ are by far the most robust. Indeed, Robula+ reduces the locators' fragility on average by 90% w.r.t. absolute locators and by 63% w.r.t. Selenium IDE locators. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, we present ROBULA+, a novel algorithm able to generate robust XPath‐based locators – locators that are likely to work correctly on new releases of the web application. We compared ROBULA+ with several state‐of‐the‐practice/art XPath locator generator tools/algorithms. Results show that XPath locators produced by ROBULA+ are by far the most robust. Indeed, ROBULA+ reduces the locators' fragility on average by 90% w.r.t. absolute locators and by 63% w.r.t. Selenium IDE locators.